Struktur Politik dan Deradikalisasi Pendidikan Agama Bagi Anak Muda di Indonesia - Ahnaf, Mohammad Iqbal (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
This paper addresses the issue of youth succeptability to radicalization that has been a major concern since report finding suggesting high number of youth support and participation in radical group. Using political opportunity theory in social movement studies, this paper discusses the macro context of radicalization among youth. It shows that changes of social and political landscape in Indonesia has motivated the shift of focus of Islamist movement toward mobilization at the social level as an alternative to failing political activism in parliament. In addition to this macro context, this paper illustrates the forms of social millie in schools that are critical to radicalization in schools. It concludes that the key to radicalization in school does not parimarily lay in religious teaching curricullum, but on condition and activities outside classroom that allow transmision of radical naratives among students.